Reduced aerosol pollution diminished cloud reflectivity over the North Atlantic and Northeast Pacific - Von,Salzen K; Akingunola,A; Cole,JNS; Digby,RAR; Doherty,SJ; Fraser-Leach,L; Gryspeerdt,E; Sigmond,M; Wood,R (Nature Communications, 2025)
Over the past several decades, the proportion of solar radiation reflected back into space has declined, accelerating the accumulation of heat within the Earth system. Here we show that the marine cloud reflectivity decreased on average by 2.8 ± 1.2% per decade in the combined North Atlantic and Northeast Pacific regions between 2003 and 2022. The majority of the Earth System Models we analyzed simulated a significantly weaker cloud reflectivity decrease and warming of the sea surface in these regions than observed. In contrast, our simulations using an improved aerosol-climate model reproduce the spatial extent and magnitude of the observed cloud reflectivity decrease. We show that reductions in sulfur dioxide and other aerosol precursors accounted for 69% (range 55−85%) of the cloud reflectivity decrease through aerosol-cloud interactions, consistent with the observed aerosol and cloud trends. This raises the prospect of a continuing cloud reflectivity decrease and an associated warming impact in these regions, given that the emission reductions are projected to persist over the next few decades. Further research is needed to assess whether near-term climate scenarios should be revised to account for the weak cloud reflectivity reductions in the Earth System Models.